2020
DOI: 10.1245/s10434-020-08303-1
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Comorbidity on Health-Related Quality of Life After Esophageal Cancer Surgery

Abstract: Background. Esophageal cancer surgery reduces patients' health-related quality of life (HRQoL). This study examined whether comorbidities influence HRQoL in these patients. Methods. This prospective cohort study included esophageal cancer patients having undergone curatively intended esophagectomy at St Thomas' Hospital London in 2011-2015. Clinical data were collected from patient reports and medical records. Well-validated cancer-specific and esophageal cancer-specific questionnaires (EORTC QLQ-C30 and QLQ-O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
2
4
0
Order By: Relevance
“…In line with the findings of Backemar et al [30], we also identified a higher ASA score as an important predictor of lower overall health status and long-term QoL. Unlike other studies, we did not find an association between other risk factors such as neoadjuvant treatment and the presence of comorbidities with impaired QoL [23, 28, 30].…”
Section: Discussionsupporting
confidence: 91%
“…In line with the findings of Backemar et al [30], we also identified a higher ASA score as an important predictor of lower overall health status and long-term QoL. Unlike other studies, we did not find an association between other risk factors such as neoadjuvant treatment and the presence of comorbidities with impaired QoL [23, 28, 30].…”
Section: Discussionsupporting
confidence: 91%
“…21,[30][31][32][33] Various studies reported that older, co-morbid, and advanced-stage cancer patients had poor HRQoL. 15,[34][35][36][37] Hence, this high burden of poor HRQoL revealed in our study could be linked to the predominance of co-morbid and advanced-stage esophageal cancer patients in our setting. In sub-Saharan Africa, cancer care is suboptimal due to the shortage of diagnostic facilities and the high cost of treatment.…”
Section: Determinants Of Hrqol Among Gastrointestinal Cancer Patientsmentioning
confidence: 55%
“…Adequate drainage after resection in these patients is particularly important to avoid clinical symptoms associated with perihepatic fluid collection, including fever and/or abdominal discomfort [42]. The Charlson Comorbidity Index (CCI) was developed to predict the prognosis of admitted patients by assessing the number of certain comorbidities and their severity and has been widely used to assess the degree of comorbidity burden [43,44]. The CCI system records some important comorbidity closely relevant in the context of elective liver surgery, including coexisting liver disease, chronic pulmonary disease, peptic ulcer disease, diabetes, moderate-tosevere renal disease and tumor.…”
Section: Plos Onementioning
confidence: 99%